Torque production improvement of a five phase fractional-slot PM machine under faulty operation. Issue 6 (2nd November 2015) - Rebai, Hajer; Abdennadher, Imen; Masmoudi, Ahmed
Abstract : Purpose: – The purpose of this paper is to deal with several approach to recover the torque production capability of a five phase double-layer fractional-slot PM machine under faulty operation. The considered fault is an open-circuit coil in a given phase. Design/methodology/approach: – In a first step, the mean futures, such as the phase back-EMFs and the electromagnetic torque, are computed by finite element analysis under healthy operation, and are taken as references. Then, they are investigated, under a faulty coil, for different approaches to recover the torque production capability. Findings: – A comparison of the potentialities of the torque recovery approaches has clearly highlight the superiority of the approach consisting in the re-adjustment of the current initial phases, in an attempt to equilibrate the resulting air gap MMF. Research limitations/implications: – This work should be extended by an experimental validation of the predicted results regarding the back-EMFs and the electromagnetic torque. Practical implications: – The investigation of the considered five phase fractional-slot PM machine under faulty operation should be extended to several faulty scenarios in order to fulfill the requirements of many applications such as the propulsion systems. Originality/value: – The paper proposes different approaches to recover the torque production capability of a five phase fractional-slot PM machine under faulty operation.